ASSESSING THE ROLE OF TECHNOLOGY AND INNOVATION IN ENHANCING PRODUCTIVITY AND REDUCING RELIANCE ON IMPORTS - M. Mohamed Shiraj; A.R.M Arshard; M. Dhuveeshan (Antis Publisher, 2025)
Objective: This study examines the role of technology and innovation in enhancing productivity and reducing reliance on imports, focusing on the challenges and opportunities for developing countries. Method: Utilizing a mixed-methods approach, the research combines quantitative data analysis of productivity indicators and trade balances with qualitative insights from expert interviews to explore the impact of technological adoption and innovative practices. Results: The findings reveal that strategic investment in technology and innovation significantly boosts productivity and decreases dependency on imported goods. However, substantial barriers, including inadequate infrastructure, skill shortages, and limited financial resources, hinder the realization of these benefits. The study identifies key policy interventions, such as increased R&D investment, improved access to capital, human capital development, and enhanced intellectual property protections, as essential for fostering an innovation ecosystem. Novelty: This research provides a comprehensive analysis of how tailored policy frameworks can effectively leverage technology and innovation to achieve sustainable economic growth in developing countries, offering a unique perspective on reducing import dependency while enhancing productivity.